PENGARUH KEPRIBADIAN DAN LINGKUNGAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DAN KINERJA TENAGA MEDIS - Semuel Kailola (Manis: Jurnal Manajemen dan Bisnis, 2019)
This study aimed to determine the effect of personality, work environment, and Organizational Citizenship Behavior (OCB) on the performance of medical workers directly and indirectly mediated by Organizational Citizenship Behavior (OCB). The population of this study were medical workers at the Sumber Hidup Hospital and Hative Hospital in Ambon City, which were 164 people. The number of samples used in this study were 116 medical workers obtained by using the Slovin formula and the sampling technique used was probability sampling with simple random sampling method. Data collection techniques were questionnaires, interviews and documentation studies. Descriptive statistical analysis, path analysis using SPSS for windows version 23 were applied as a data analysis method. The results showed that there was a positive and significant direct influence of personality on Organizational Citizenship Behavior (OCB) with a significance value of 0.005 < 0.05. There was a positive and significant direct influence of the work environment on Organizational Citizenship Behavior (OCB) with a significance value of 0.001 < 0.05. There was a direct positive and significant influence of the medical workers performance with a significance value of 0.002 < 0.05. There was a positive and significant direct influence of the work environment on the medical workers performance with a significance value of 0.001 < 0.05. There wass a positive and significant direct influence of Organizational Citizenship Behavior ( OCB) on the medical workers performance with a significance value of 0.008 < 0.05. Organizational Citizenship Behavior (OCB) mediated the relationship of personality to medical workers performace was (0.343 > 0.282). While Organizational Citizenship Behavior (OCB) mediated the relationship of the work environment to the medical workers performace (0.374 > 0.299) so that H1, H2, H3, H4, H5, H6 , and H7 were accepted.